ANALISIS KEMAMPUAN STOCK SELECTION DAN MARKET TIMING MANAJER INVESTASI PADA REKSADANA SAHAM DI INDONESIA - PANJAITAN, MICHAEL VINCENTIUS (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2012)
The purpose of this study is to analyze equity fund performance in Indonesia. Performance of mutual fund manager is measured by stock selection skill and market timing ability. This research was done to test the ability of investment manager to create portfolio that have outperform return market by stock selection skill and market timing determination. Sample uses in the research are 51 equity funds listing in Bursa Efek Indonesia BAPEPAM-LK during 2009-2012. The results of stock selection showed that the majority of equity of fund manager Indonesia, have an inferior skill in stock selection. Becuse only 2 mutual fund that have positive and significant alpha. Beside the results show that majority of equity fund manager Indonesia, have an inferior skill in determining market timing. Using Treynor-Mazuy model it found that 6 that signifigant and using Henriksson-Merton it found that 9 have significant positive alpha